Avaliação do dano por choque térmico em concretos refratários via espectroscopia acústica ressonante não-linear - Pereira, Antônio Henrique Alves (Universidade Federal de São Carlos, 2012)
In this thesis the Non-linear Resonant Acoustic Spectroscopy Technique used to evaluate the mesoscopic non-linearity was incorporated into the Impulse Excitation Technique, which is extensively applied to the evaluation of thermal shock damage of refractory castables by the characterization of dynamic elastic moduli. The motivation for this thesis was the mesoscopic non-linearity detection in refractory castables and the interest for more sensitive techniques for thermal shock damage assessment, as well as detecting cracks and microcracks. An experimental apparatus able to evaluate the non-linearity was developed, which allowed the simultaneous characterization of the dynamic elastic moduli and damping with different amplitudes of excitation. The apparatus error was evaluated using the characterization of synthesized signals and it is lower than 0.05 % for frequency, 3.3 % for damping and 2 % for amplitude. The technique association was applied to the evaluation of thermal shock damage resistance of refractory castables made with white fused alumina aggregates of 2.4 mm maximum size (A2) and of 8.0 mm maximum size (A8), and of a refractory castable made with tabular alumina aggregates of 3 mm maximum size (AT). The A2 castable showed similar thermal shock resistance to the AT one due to the configuration of cracks and microcracks, which occurred in the matrix. The technique association was also used to evaluate different thermal shock types and the moisture influence. The results showed that the primary source of damage is the thermal shock of cooling and that the moisture has a significant influence in the elastic property characterization (up to -9.4 % for the Young's modulus and +35 % for damping). The information provided using the non-linearity characterization was similar to the retained Young's modulus, however regardless of previous characterizations. This allowed a more accurate assessment of the damage than using the Impulse Excitation Technique alone.
Evaluation of thermal shock damage of refractory castables using the non-linear resonant acoustic spectroscopy
Keywords: Propriedades mecânicas; Não-linearidade; Choque térmico; Concretos refratários; Técnica de excitação por impulso; Módulo de elasticidade; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA